La falta de disposición y de capacidad de los sistemas judiciales domésticos, en el marco del principio de complementariedad (2009)
When pass the test of complementarity, the notions of lack of willingness and of capacity are erecting as decisive for the admissibility of a situation and a case of which is derived, before the International Criminal Court. Of course, determining the reach of such expressions i largely normative and, for its realization, the Rome’ Statute of the International Criminal Court provides a range edges whose meaning, by the hand of the doctrine and jurisprudence, seeks to elucidate